2018
DOI: 10.1038/s41598-018-27794-3
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro potency assay using nicotinic acetylcholine receptor binding works well with antivenoms against Bungarus candidus and Naja naja

Abstract: In order to facilitate/expedite the production of effective and affordable snake antivenoms, a novel in vitro potency assay was previously developed. The assay is based on an antiserum’s ability to bind to postsynaptic neurotoxin (PSNT) and thereby inhibit the PSNT binding to the nicotinic acetylcholine receptor (nAChR). The assay was shown to work well with antiserum against Thai Naja kaouthia which produces predominantly the lethal PSNTs. In this work, the assay is demonstrated to work well with antiserum/an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…The receptor blocking assay was adapted from Ratanabanangkoon et al . 36 Black MaxiSorp plates (Nunc) were coated overnight with 100 µL of 5 µg/mL human α7-acetylcholine receptor chimera (adapted from Ref. 37 ) in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…The receptor blocking assay was adapted from Ratanabanangkoon et al . 36 Black MaxiSorp plates (Nunc) were coated overnight with 100 µL of 5 µg/mL human α7-acetylcholine receptor chimera (adapted from Ref. 37 ) in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…The receptor blocking assay was adapted from Ratanabanangkoon et al (35) . Black Maxisorp plates (Nunc) were coated overnight with 100 µL of 5 µg/mL human α7-acetycholine receptor chimera (adapted from (36) ) in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have reported the ability of a N. kaouthia PLA 2 to block acetylcholine currents in Lymnaea stagnalis neurons or to compete with α-bungarotoxin for binding to Torpedo or α7-type receptors (Vulfius et al, 2014). The purified Torpedo nAChR has also been employed in in vitro assays to assess antivenom efficacy against the venoms of N. kaouthia (Thai monocled cobra), N. naja (Indian cobra), and B. candidus (Malayan krait) (Ratanabanangkoon et al, 2017, Ratanabanangkoon et al, 2018).…”
Section: Introductionmentioning
confidence: 99%